UJI KONSENTRASI EKSTRAK TEPUNG DAUN SIRSAK (Annona muricata L) UNTUK MENGENDALIKAN HAMA PENGGEREK BUAH KAKAO (Conopomorpha cramerella SNELLEN.) PADA TANAMAN KAKAO (Theobroma cacao L) DI PADANG PARIAMAN - Rusli Rustam; Revi Hariyati (Jurnal Agroekoteknologi, 2021)
Cocoa (Theobroma cacao L.) is a plantation crop that has an important role in the national economy. Conopomorpha cramerella Snellen is a pest that causes a decrease in cocoa production in the field. The recommended control is using botanical insecticides using soursop leaves (Annona muricata L). This study aimed to obtain best concentration of soursop leaf flour extract (A. muricata L) to control the attack of cocoa pod borer (C. cramerella Snellen) in the field. The research was conducted in the garden of residents of Nan Sabaris District, Padang Pariaman Regency, from July to October 2019. The research was carried out experimentally using a completely randomized design (CRD) with 6 treatments and 4 replications. Treatment of the concentration of soursop leaf powder extract given in each experimental unit was 0 gl-1 water, 20 gl-1 water, 40 gl-1 water, 60 gl-1 water, 80 gl-1 water and 100 gl-1 water. The results showed that soursop was able in controlling CPB (C. cramerella) pests at a concentration of 100 gl-1 water which reduced the percentage of affected fruit to 10% with the lowest fruit damage intensity, namely 12.48%, the largest fruit diameter was 18.15 cm, with the smallest larval population of 0.75 tails, and the maximum dry weight of seeds reaching 150.75 g.